The Mathematics Creative Thinking Skills on the Connecting, Organizing, Reflecting, and Extending (CORE) Learning Model Seen from Students Independence Assisted by Contextual Module - Endah Agustina, Rini Afifah; Sukestiyarno; Dwijanto (Universitas Negeri Semarang, 2024)
The goal of this research is to pinpoint the underlying factors contributing to students' poor mathematical creative thinking skills and to evaluate the impact of CORE learning with contextual modules on these skills. This research method uses a mixed-method approach with a sequential exploratory strategy, which involves the sequential collection of qualitative and quantitative data. The population in this study is the seventh-grade students of SMP N 3 Kandangan for the 2021/2022 academic year. The researchers collected data through observation, interviews, tests, and questionnaires. The researchers analyzed the data descriptively, using both qualitative and quantitative methods. The research findings indicate that the CORE learning model, in conjunction with contextual modules, can effectively address the factors contributing to low mathematical creative thinking skills. CORE learning assisted by contextual modules is effective in terms of student independence. The skills to think creatively in mathematics during CORE learning assisted by contextual modules shows that students achieve above the Minimum Completeness Criteria (KKM) of 70. When students think creatively in mathematics during CORE learning with contextual modules, their completeness surpasses the KKM by more than 75%, resulting in a 31% improvement on the Gain Test. Students with high independence are able to meet all four indicators of mathematical creative thinking skills, namely fluency, flexibility, originality, and elaboration. Students with low or very low independence can only meet two or three indicators of mathematical creative thinking skills, such as fluency, flexibility, and originality, but are unable to meet one of the other indicators.